Mid-term development of hamstring tendon length and velocity after distal femoral extension osteotomy in children with bilateral cerebral palsy: a retrospective cohort study - Salami, Firooz; Klotz, Matthias C. M.; Dreher, Thomas; Wolf, Sebastian Immanuel; Thielen, Mirjam (Developmental medicine and child neurology, 2018)
Aim Flexed knee gait can be treated with distal femoral extension osteotomy (DFEO) and additional patellar tendon advancement (PTA) in children with cerebral palsy (CP). This study assesses changes in hamstring muscle tendon length (MTL) and velocity after DFEO (+PTA). Method Nineteen children (mean age 13y [standard deviation 3y] at surgery) with CP and flexed knee gait who were treated with DFEO (15 limbs) or DFEO+PTA (10 limbs) were retrospectively included in this study. Gait analyses were performed preoperatively (E0), 1 year postoperatively (E1), and for 10 limbs additionally 2 to 5 years postoperatively (E2). Hamstring MTL and velocities were assessed at all examination dates using OpenSim. Results Hamstring MTL and velocity did not change significantly over time. From E0 to E1, knee flexion in stance improved for both DFEO and DFEO+PTA (p<0.05), knee flexion in swing only improved after DFEO+PTA (p<0.05). The improved knee flexion in stance and swing was maintained at E2. Interpretation DFEO led to a significant improvement in knee kinematics at E1 which was maintained at E2. DFEO seems to prevent recurrent hamstring tightness but does not lead to lengthened or fastened hamstrings. What this paper adds Distal femoral extension osteotomy (DFEO) does not change hamstring muscle tendon length. DFEO does not change hamstring lengthening velocity. DFEO leads to a significant improvement in knee kinematics. Changes in knee kinematics after DFEO can be maintained at mid-term. DFEO seems to prevent recurrent hamstring tightness.
Gesehen am 15.05.2019